A new species of Neoeutrypanus Monné, 1977 from Guatemala (Coleoptera, Cerambycidae) - Monné, Miguel A.; Botero, Juan Pablo (Zootaxa, 2017)
Neoeutrypanus Monné, 1977 was reviewed by Botero & Monné (2015); currently, the genus is composed by 12 species, distributed from Mexico to the north of Argentina (Monné, 2017). Herein, we describe a new species from Guatemala and a modify the key proposed by Botero & Monné (2015) to include the new species.